HUBUNGAN KERAPATAN MANGROVE DENGAN KELIMPAHAN GASTROPODA DI KAWASAN KONSERVASI MANGROVE DAN BEKANTAN (KKMB) KOTA TARAKAN - Gazali, Salim; Rachmawani, Dori; Agustianisa, Rahmah (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2019)
Mangrove forests are one of the natural ecosystems that make a large contribution to the population as a food source, one of which is gastropods. The purpose of this study was to determine the density of mangroves, the abundance of gastropods and the discussion between the density of mangroves and the abundance of gastropods. This research was carried out in September - November 2018 in the area of 12 ha KKMB. The research method used was a survey method by conducting direct research on 12 plot points with a plot size of 10 x 10 meters were in each plot there were 3 sub-plots made 1 x 1 meter randomly carried out in the plot to take gastropod samples. The collected data are grouped by type variable, mangrove density as a variable (X) and gastropod abundance as a variable (Y). The results showed that the mangrove yields in the area obtained by KKMB belonged to the very solid (good) category with a value of 11.700 ind / ha. The highest gastropod abundance is dominated by the type of Cassidula aurisfelis with the number of 79 individuals Â and the lowest abundance of the type Littoraria scabra with the number of 14 individuals . The low level of gastropod abundance is reduced due to the low density of mangrove species and the low food source in the mangrove area. The relationship of mangrove density with gastropod abundance using simple linear regression analysis obtained the value of determination coefficient (R2) of 0.227, while the coefficient value was 0.4766 which means that it is positively correlated.